Analisis Wacana Kritis Pada Berita Nadiem Tegaskan Kenaikan UKT Berlaku Bagi Mahasiswa Baru Pada Idntimes.Com - Putri Enjel Tarigan; Yandika Lamtorang Gurusinga; Yemima Rina Yanti Panjaitan; Mustika Wati Siregar (Simpati, 2024)
This research aims to conduct critical discourse analysis of news regarding the increase in UKT only applicable to new students presented by the IDN Times media. The research method used is qualitative descriptive analysis using the scalpel of critical discourse analysis developed by Norman Fairclough who views discourse as text. The research results show that the news was conveyed well and clearly by the IDN Times media, and was considered positive, especially for students who were not yet economically established. Macrostructural analysis also reveals that there are differences of opinion in society regarding this policy, with the media and the figure of Nadiem playing an important role in presenting information to the public.